Finance and Development, December 2018. (Finance and Development; Finance and Development ;, 2018)
This paper focuses on overcoming fears of technology and globalization means rethinking the rights and obligations of citizenship. While the causes of our discontent vary, they all point to the need to revitalize politics, economics, and social contract to provide citizens with a greater sense of security and confidence in the face of impending changes. The backlash highlights the need for a new social contract, one that adapts to changed economic realities and better manages the social implications of globalization. The social contract includes the payment of taxes in exchange for public goods, and the way that society looks after the old, the young, the infirm, and those who have fallen on hard times. Countries with greater social mobility grow faster because they more effectively match people to the right jobs. Another way to address inequality would be to put a floor under incomes, which would help ensure that even low-wage earners can enjoy a reasonable standard of living.